Success of re-introduced Sphagnum in a cut-away peatland - Tuittila, E.-S.; Vasander, H.; Laine, J. (Boreal Environment Research Publishing Board, 2024)
In a four-year field experiment, we studied the establishment success of re-introduced Sphagnum angustifolium in a restored (rewetted) cut-away peatland. The importance of (1) the presence of capitula and (2) water table level for re-colonisation was tested. The ten times greater cover produced by moss material with capitula revealed that using only the top few centimetres of moss surface the re-colonisation success can be remarkably accelerated. Each year the mean cover was higher in drier conditions than in the regularly flooded conditions. Similarly the length of mosses increased more evenly in drier conditions. The weaker establishment at wetter conditions was a result of peat erosion and the disappearance of mosses due to periodical flooding. The development of Sphagnum carpet was not linear but the cover decreased during years with periods of flooding and drought. The dynamic state of the Sphagnum surfaces showed that the moss cover was not permanently established during the four years study period, but was sensitive to variation in water table level.